Perlindungan Hukum terhadap Perempuan sebagai Korban penyebaran Konten Asusila di Media Elektronik - Margareth Horman (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research aims to determine the form of legal protection for women as victims of the dissemination of immoral content and to determine whether existing regulations are effective in restoring victims' conditions. This research uses a normative legal research method that focuses on reviewing and analyzing regulations related to the title. The results of this research reveal that existing regulations are still insufficient to provide protection and recovery for victims because they still focus on punishing perpetrators, ignoring the victims' interests. Therefore, regulatory updates are needed that focus on the interests of victims, so that protection in terms of victim recovery can be implemented effectively.